2019
DOI: 10.1108/ijbm-04-2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Examining consumers’ usage intention of contactless payment systems

Abstract: Purpose The purpose of this paper is to develop and test a conceptual model that combines the modified Unified Theory of Acceptance and Use of Technology (UTAUT2) with a consumer brand engagement (CBE) model to predict consumers’ usage intentions toward contactless payment systems in a developed country. Design/methodology/approach The authors cooperated with a contactless payment service provider in Finland and reached out to 22,000 customers, resulting in 1,165 usable responses. The collected data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 79 publications
15
119
2
2
Order By: Relevance
“…In this regard, this result concurred with the TAM model suggested by Davis [15]. Moreover, this study outcome concurred with existing literature in the mobile payment system area (e.g., [10,11,29,30,47]). Those studies state that increasing perceived usefulness lead to an increased behavioral intention to use those systems.…”
Section: The Effect Of Perceived Usefulness On Intention To Use Mobile Payment Systemsupporting
confidence: 90%
“…In this regard, this result concurred with the TAM model suggested by Davis [15]. Moreover, this study outcome concurred with existing literature in the mobile payment system area (e.g., [10,11,29,30,47]). Those studies state that increasing perceived usefulness lead to an increased behavioral intention to use those systems.…”
Section: The Effect Of Perceived Usefulness On Intention To Use Mobile Payment Systemsupporting
confidence: 90%
“…Contactless payment can be described as any payment transaction that requires and absence of physical contact between the consumer's payment device and the physical terminal [22]. Karjaluoto et al (2019) [23] pointed out the difference between "contactless payment" and "remote payment," where the remote payment method uses cellular networks (or WiFi) during payment transactions, while contactless payment generally utilizes near-field communication (NFC) technology, which does not require an internet connection-allowing clients to use their NFC-enabled payment cards and smartphones instead of paying with banknotes or swiping credit cards at the POS terminal. The survey of consumers in March 2020 revealed that having a contactless feature on their credit card was a necessary feature [24], since cardholders are looking toward contactless and digital wallets as safer alternatives.…”
Section: -3-contactless Payment Technologymentioning
confidence: 99%
“…Further, Marous ( 2013 ) identified that encouraging customers to change the current banking channel is a difficult venture. Similarly, Karjaluoto et al ( 2019 ) asserted that customers’ intention to use contactless payment systems is highly influenced by habit and it is hard to change such behaviours. The best alternative at this stage that the bank could have is to set up an optimal channel mix to meet customers banking needs.…”
Section: Conceptualisation Of In-branch Efforts and Technology Acceptmentioning
confidence: 99%